Analysis of the Effect of Green Marketing and Environmental Knowledge on Purchase Intentions Mediated by Brand Image - Achmad Syauqi Ilal JINAN; Surachman SURACHMAN; Djumahir DJUMAHIR (International Journal of Environmental, Sustainability, and Social Science, 2022)
that becomes equipment to support people's daily activities can lead to various environmental problems such as environmental pollution. With the rapid growth of single-use products with pressure from global organizations, environmentally friendly products have emerged which are expected to be a solution to minimize environmental pollution and natural disasters. This study aims to analyze the effect of green marketing and environmental knowledge on purchase intention which is mediated by brand image on boxed tea products. In this study, data collection was obtained by using an online questionnaire. The sample in this study used students who were doing undergraduate or diploma studies and domiciled in Malang as many as 107 respondents. The results of this study show that green marketing has no significant effect on purchase intention, green marketing has a significant effect on brand image, green marketing mediated by brand image has a significant effect on purchase intention, environmental knowledge has a significant effect on purchase intention, environmental knowledge has a significant effect on brand image, environmental knowledge has a significant effect on purchase intention mediated by brand image. The findings of this study suggest that companies in Indonesia with single-use products pay attention to the impact of waste from these products on nature.